PEMODELAN INVERSI ANOMALI MAGNETIK 3D DAERAH MATA AIR PANAS DIWAK DAN DEREKAN - Siti Zulaikhah; Udi Harmoko; Tony Yulianto; Gatot Yulianto; Sugeng Widada; Yusuf Dewantoro (Youngster Physics Journal, 2016)
Research of magnetic methods that aim to interpretation the subsurface structure around the hot springs area Diwak and Derekan and to identification caused of hot springs Diwak and Derekan has been successfully carried out. In this research, measurements were taken at 97 points using a proton precession magnetometer (PPM) type of GSM model 19T geometrics and two Geotron Magnetometer G5 models to get the value of the total magnetic field. Measurement data is processed by the daily variation correction and correction IGRF (International Geomagnetic Reference Field) to get the value of the total magnetic field anomaly. Corrected data used to create contours of the total magnetic field anomaly. Contour total magnetic field anomaly is used for the reduction to plan surface process and upward continuation process. The results of the upward continuation get the contours of local anomaly and regional anomaly, the results of the local anomaly contour then reduced to the pole. Results of the research is a pair of positive and negative closure indicate a fault structure below the surface. There are two pairs of positive and negative closure which an incision is made to determine the subsurface structure by creating a 2D model using the software Mag2dc. 2D modeling results indicate the existence of a second incision fault structure in the form of down trending fault southwest-northeast. Meanwhile, to make 3D models using software Mag3D and 3D modeling results indicate the presence of fault structures below the surface. Fault zone results of 2D and 3D modeling is a media outlet fluid to the surface in the form of hot springs Diwak and Derekan.